EFEK PEMBERIAN DOSIS TIMBAL (Pb) TERHADAP MORFOLGI DAN PERTUMBUHAN 2 JENIS TANAMAN SAYURAN - nur qowiy wijayanti (AGRONISMA, 2020)
Industry waste, agriculture waste, and domestic waste are either source of environment pollution. The pollution that happened can make the soil pollution, because the heavy metal who contained in soil, the heavy metal concentration in soil can be neutralized by the phytoremediation is called hyperaccumulator plants. In the some research kale and spinach which has the ability as plants who reducing the impact of environmental pollution as a hyperaccumulator plants. The purpose of this research is looking at the effect of lead on the morphology and growth of kale and spinach who added the dose of lead in soil, the dose are 0 mg/kg, 200 mg/kg and 400 mg/kg. The design of this research is Randomized Block Design with Factorial, the first factor is plants and the second factor is the different dose of lead. This research showed there are the morphological changes of the kale and spinach plant who added by dose of lead 200 mg/kg and 400 mg/kg dose of lead. If the dose of lead is increase so the morphological change will be higher.